2020
DOI: 10.1186/s12877-020-01668-8
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition assessment and geriatric associated conditions among community dwelling Iranian elderly people

Abstract: Background: Although malnutrition risk is well documented in elderly care institutions, few studies have been conducted to address concerns regarding community-dwelling elderly people. This study has been aimed to describe the nutritional status and its related socioeconomic and geriatric factors in community-dwelling elders with malnutrition. Method: For this study, a randomized sampling among people aged 60 has been done (n = 326). Information on nutrition status (full MNA) and health information, like cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 37 publications
6
31
0
1
Order By: Relevance
“…Malnutrition has been linked with poor functional status as it is an important contributor toward increased vulnerability for developing negative health outcomes, loss of independence, and mortality ( 18 , 43 ). Meal preparation and eating disabilities seem to be the main cause of malnutrition in older adults with poor functional status ( 44 ). Our study showed a positive and significant effect of functional status on the MNA score.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition has been linked with poor functional status as it is an important contributor toward increased vulnerability for developing negative health outcomes, loss of independence, and mortality ( 18 , 43 ). Meal preparation and eating disabilities seem to be the main cause of malnutrition in older adults with poor functional status ( 44 ). Our study showed a positive and significant effect of functional status on the MNA score.…”
Section: Discussionmentioning
confidence: 99%
“…FCs’ impaired nutritional status could compromise the successful care of a CR for several reasons. Decreased nutritional status is related to decreased functional ability [ 2 , 5 ], such as decreased physical performance [ 5 ] and difficulties in daily activities such as shopping and cooking [ 6 , 7 , 8 , 9 ]. Impaired nutritional status is also related to decline in cognition [ 2 , 8 ] and depressive symptoms [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased nutritional status is related to decreased functional ability [ 2 , 5 ], such as decreased physical performance [ 5 ] and difficulties in daily activities such as shopping and cooking [ 6 , 7 , 8 , 9 ]. Impaired nutritional status is also related to decline in cognition [ 2 , 8 ] and depressive symptoms [ 10 , 11 ]. This association between nutritional status and depressive symptoms has also been shown in studies with older FCs [ 1 , 2 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, nutrition is another important dimension of self‐care behaviour that affects all aspects of the life of the elderly. Malnutrition problems are serious in the elderly group and can lead to many health concerns, including weakness, a compromised immune system, increased risk of infection, muscle weakness and bone loss, followed by increased falls and increased risk of hospitalization and death 10 . The prevalence of malnutrition among various populations of the elderly is reported to be between 18% and 30% 11 .…”
Section: Introductionmentioning
confidence: 99%